A solution for improved simulation efficiency of a multi-domain marine power system model. (12th April 2010) - Schuddebeurs, Jeroen D.; Norman, Patrick J.; Elders, Ian M.; Galloway, Stuart J.; Booth, Campbell; Burt, Graeme; Apsley, Judith
Integrated Full Electric Propulsion (IFEP) marine power systems offer increased design flexibility and operational economy by supplying ship propulsion and service loads from a common electrical system. Predicting the behaviour of IFEP systems through simulation is important in reducing the design risk. However, the prevalence of power electronics and the potential for interaction between large electrical and mechanical systems introduce significant simulation challenges. This paper presents an integrated simulation tool, which brings together electrical, mechanical, thermal and hydrodynamic models, facilitating a holistic simulation capability. Approaches adopted for model validation and computational efficiency together with two case studies are discussed.